The Study of Incidence and Characteristics of Patients with Eye-Related Chief Complaints at the Emergency Department of Thammasat University Hospital. (19th October 2020) - Imsuwan, Intanon; Amnuaypattanapon, Kumpol; Vongkittirux, Sakchai; Imsuwan, Yutthaphong
Abstract : Background . Patients with eye-related chief complaints could be diagnosed not only with eye diseases but also with noneye diseases. This study determines rates and characteristics of patients with eye-related chief complaints at the Emergency Department of Thammasat University Hospital. Methods . The study design is a descriptive retrospective observational study of patients with eye-related chief complaints at the Emergency Department of Thammasat University Hospital in 2017. Demographic data, diagnosis, management, consultation, and disposition were recorded by chart review. Categorical data were reported by percentage. Results . Of the 52081 patients, 704 (1.3%) presented with eye problems. 60% of the patients were males. Patients were classified into three groups which are traumatic eye disease, nontraumatic eye disease, and noneye disease. 75.9% of the patients suffered traumatic injuries. The most common diagnoses of the traumatic eye injuries were foreign bodies at the cornea and conjunctiva and minor trauma to the conjunctiva. The most common mechanisms were foreign bodies in the eyes, cuts, or pierces. The most common causes of the injuries were from metals and housewares. The most common nontraumatic eye diagnoses were conjunctivitis and corneal ulcer. The most common noneye diagnoses were exposure of healthcare providers to secretions from patients, angioedema, and hypertensive crisis. Conclusions . Most of the patients who came to the ER with chief complaints of the eyes could be treated by doctors in the emergency room without consulting ophthalmologists. Chief complaints of the eyes could be the leading symptoms of many organ systems. Emergency physicians should be differentially diagnosed to cover neurologic, cardiovascular, and immunologic problems.